APLIKASI PAJAK PENGHASILAN (PPH) PASAL 21 (STUDI PADA PD. BPR BANK DAERAH LAMONGAN) - Helmi, Alfian; Anniswati, Isnaini (Majalah Ekonomi, 2019)
PD. BPR Bank Daerah Lamongan is a bank that is known to serve micro, small and medium entrepreneur groups with locations that are generally close to where people in need. PD. BPR Bank Daerah Lamongan is also known as market bank, PD. BPR Bank Daerah Lamongan employ many employees, PD. BPR Bank Daerah Lamongan is a company that cuts income tax and counts the income tax that has to be paid by the employees. However the rarity of the calculation of the tax survey will make the tax tend to be the same. This could harm the taxpayer and the state as the receiver of taxes. The purpose of this research is to know how the application of income tax point 21 on the employees of PD. BPR Bank Daerah Lamongan and how the income tax of point 21 on the employees PD. BPR Bank Daerah Lamongan is counted. The method used by the researchers is descriptive qualitative research methods, descriptive qualitative research is a procedure that produces descriptive data in the form of words written or spoken of the people and behaviors that can be observed. The results of the study were deduction of the income tax that has to be paid by on employees of PD. BPR Bank Daerah Lamongan each month. The income tax each month is different because of differences in income received by the employee. This difference is due to the differences in the benefits received by the employee each month. The rarity of tax survey conducted by the company make the calculation of income tax be the same every month, even though the employee may be married or has a new dependents (children).